2008
DOI: 10.1007/s11249-008-9334-1
|View full text |Cite
|
Sign up to set email alerts
|

Disk Lubricant Additives, A20H and C2: Characteristics and Chemistry in the Disk Environment

Abstract: Disk lubricant additives A20H and C2 are Fomblin Z type perfluoropolyether with the hydroxyl endgroup, -O-CF 2 -CH 2 -OH, at one end, and the cyclo-triphosphazene end-group, R 5 (PN) 3 -O-, at the other end. Here, R is an m-trifluoromethyl-phenoxy group for A20H and a trifluoroethoxy group for C2. These additives were examined for miscibility with benzene, spin-off rate, water contact angle, and the diffusion rate over the carbon overcoat. It is revealed that A20H adheres to the carbon overcoat spontaneously. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…The bonded ratio of Z-tetraol increased slightly with photoelectron-assisted UV irradiation; however, that of ADOH increased drastically with UV irradiation. This result agrees with the results of previous work, where the cyclo-triphosphazene end group of ADOH was more sensitive to photoelectron chemical reaction than the hydroxyl end groups of other lubricants [10].…”
Section: Bonded Ratio After Uv Irradiationsupporting
confidence: 93%
See 1 more Smart Citation
“…The bonded ratio of Z-tetraol increased slightly with photoelectron-assisted UV irradiation; however, that of ADOH increased drastically with UV irradiation. This result agrees with the results of previous work, where the cyclo-triphosphazene end group of ADOH was more sensitive to photoelectron chemical reaction than the hydroxyl end groups of other lubricants [10].…”
Section: Bonded Ratio After Uv Irradiationsupporting
confidence: 93%
“…Z-tetraol has hydroxyl end groups, and ADOH has a cyclo-triphosphazene end group with an m-trifluoromethyl-phenoxy single end group. Kasai and Wakabayashi [10] indicated that the cyclo-triphosphazene end group of ADOH was more sensitive to photoelectron chemical reaction than hydroxyl end groups. Thus, ADOH should show a higher bonded ratio with photoelectron-assisted UV irradiation than Z-tetraol, because cyclo-triphosphazene end groups are easily dissociated by photoelectrons.…”
Section: Magnetic Disk Samplesmentioning
confidence: 99%
“…Separately we reported on characterization of lubricant additives A-20H and C2 [2]. Shown below are their chemical formulae.…”
Section: Introductionmentioning
confidence: 99%
“…(1) Lewis basicity (electron donating property) of the triphosphazene moiety of these lubricants prevents the catalytic degradation of PFPE backbone. (2) A20H adheres to the carbon overcoat spontaneously while C2 does not. (3) Irradiation of disks lubricated with A20H with short UV (k = 185 nm) results in detachment of phenoxy unit(s) and attachment of the remaining molecular chain to the carbon overcoat.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation